Symbols of Abuse of Power in Muhammad Ramadhan Batubara’s Short Story "Pesan dari Seorang yang Bernama Presiden" - Putri, Diantri Seprina; Aryana , Suhud; Rachman, Aditya; Sari, Hanifah Yulia; Ulya, Ridha Hasnul (JLER (Journal of Language Education Research), 2025)
In literary works, the language represented through words in the text is an interesting object to be analysed. This is due to the uniqueness of literary language which is different from other written languages. Language in literature is often written into certain symbols that contain hidden meanings far beyond their literal meaning. The short story Pesan Dari Seorang Yang Bernama Presiden uses a language full of symbols that need to be interpreted first using semiotic theory in order to understand the meaning of the entire text. The purpose of this study is to reveal the symbols that imply power abuse committed by a character named Presiden. The results found that the symbols of power abuse can be found in the names of the characters, the use of dogs as the Presiden's pets, and the message conveyed by the Presiden. These three results reveal that this short story contains many symbols and allusions that reveal how the character of the Presiden without getting his own hands dirty has committed power abuse against citizens by using the power he has.